2014
DOI: 10.1097/bor.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of anti-gout agents

Abstract: In general, treatments for gout are well tolerated, although clinicians must keep in mind the potential for drug interactions and the contribution of comorbidities to the potential for adverse effects with gout therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…Therefore, adherence to urate‐lowering therapy is a key issue in the management of gout. As documented in the medical literature, adherence to allopurinol is a major issue, which is partly related to its tolerability profile . The estimated incidence of adverse reactions ranged from 2% to 8% of users, including hypersensitivity reactions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adherence to urate‐lowering therapy is a key issue in the management of gout. As documented in the medical literature, adherence to allopurinol is a major issue, which is partly related to its tolerability profile . The estimated incidence of adverse reactions ranged from 2% to 8% of users, including hypersensitivity reactions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutically used XO inhibitors suppress the production of uric acid, allowing for renal excretion of the uric acid precursors xanthine and hypoxanthine prior to the formation of uric acid. Allopurinol, a purine analog and prototype XO inhibitor which has been in use since 1966, is efficacious, but its relatively low potency (IC 50 : 0.2 – 50 µM; [6]) requires dosages that can cause undesirable side effects, ranging from mild gastrointestinal upset to more severe hypersensitivity reactions and renal toxicity [912]. Even though a number of promising alternative treatments of hyperuricemia such as recombinant uricase therapy, the use of interleukin-1 inhibitors, or the targeting of renal urate transporters are currently explored [1315], XO inhibitors still remain first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Gout treatment guidelines recommend the use of colchicine, systemic corticosteroids, or NSAID for the prevention and treatment of gout flares 3,10 . While colchicine and NSAID are effective for treating flares, they are poorly tolerated or contraindicated in most patients 11 . A study indicated that > 90% of patients with gout had at least 1 contraindication to NSAID and systemic steroids, and > 30% had at least 1 contraindication to colchicine 25 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Therefore, guidelines 3,10 recommend that patients initiating ULT take antiinflammatory compounds such as colchicine, systemic corticosteroids, or nonsteroidal antiinflammatory drugs (NSAID) for flare prophylaxis. These antiinflammatories are themselves poorly tolerated, potentially unsafe, and contraindicated in many patients with gout 11 . Thus, there is a pressing need for new gout treatments that provide better SUA and flare controls.…”
mentioning
confidence: 99%